2021
DOI: 10.1002/ehf2.13683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luseogliflozin on estimated plasma volume in patients with heart failure with preserved ejection fraction

Abstract: Aims Sodium glucose co‐transporter 2 inhibitors have diuretic effects in both patients with glycosuria and with natriuresis. We sought to assess the effect of luseogliflozin on estimated plasma volume (ePV) in patients with type 2 diabetes and heart failure with preserved ejection fraction (HFpEF). Methods and results This study was a post‐hoc analysis of the MUSCAT‐HF trial (UMIN000018395), a multicentre, prospective, open‐label, randomized controlled trial that assessed the effect of 12 weeks of luseoglifloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…On the basis of a comprehensive review, we identified 15 studies that evaluated the effect of SGLT2 inhibitors on plasma volume (Table 2). 64,[72][73][74]78,[98][99][100][101][102][103][104][105][106][107][108][109] Unfortunately, most studies estimated changes in plasma volume using the Kaplan-Hakim and Strauss formulae, which cannot be applied to the evaluation of changes produced by SGLT2 inhibitors. Four reports 64,72,74,109 used indicator dilution methods, and of these, 3 were double blind and placebo controlled.…”
Section: Effect Of Sglt2 Inhibitors On Plasma and Blood Volume In Cli...mentioning
confidence: 99%
“…On the basis of a comprehensive review, we identified 15 studies that evaluated the effect of SGLT2 inhibitors on plasma volume (Table 2). 64,[72][73][74]78,[98][99][100][101][102][103][104][105][106][107][108][109] Unfortunately, most studies estimated changes in plasma volume using the Kaplan-Hakim and Strauss formulae, which cannot be applied to the evaluation of changes produced by SGLT2 inhibitors. Four reports 64,72,74,109 used indicator dilution methods, and of these, 3 were double blind and placebo controlled.…”
Section: Effect Of Sglt2 Inhibitors On Plasma and Blood Volume In Cli...mentioning
confidence: 99%
“…Sodium-glucose co-transporter-2 inhibitors have some benefits beyond their glucose-lowering effects, such as promoting natriuresis and osmotic diuresis based on glycosuria. These effects advantageously affect patients with HF as they decrease cardiac preload and improve prognosis [ 69 , 70 , 71 , 72 , 73 , 74 ]. Thus, current guidelines for the management of HF recommend the use of sodium-glucose co-transporter-2 inhibitors for patients with both HF with reduced ejection fraction and HF with preserved ejection fraction regardless of the presence of diabetes mellitus [ 44 ].…”
Section: Medical Therapy For Cvd and Liver Damagementioning
confidence: 99%
“…Liver stiffness measured with shear wave elastography has been used to evaluate liver fibrosis non-invasively [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. A shear wave is generated by inducing a push pulse of an ultrasound wave, which deforms a part of the tissue.…”
Section: Clinical Applicationsmentioning
confidence: 99%